Pathogenic Bacterial Proteins and their Anti-Inflammatory Effects in the Eukaryotic Host - Sun, Jun (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2009)
Bacteria use multiple strategies to bypass the inflammatory responses in order to survive in the host cells. In this review, we discuss the mechanism of the bacerial proteins in inhibiting inflammation. We highlight the antiinflammatory roles of the type three secretion proteins including Salmonella AvrA, Enteropathogenic Escherichia coli Cif, and Yersinia YopJ, Staphylococcus aureus extracellular adherence protein, and Chlamydia proteins. We also discuss the research progress on the structures of these anti-inflammatory bacterial proteins. The current therapeutic methods for diseases, such as inflammatory bowel diseases, sclerosis, lack influence on the course of chronic inflammation and infection. Therefore, based on the molecular mechanism of the anti-inflammatory bacterial proteins and their 3-Dimension structure, we can design new peptides or non-peptidic molecules that serve as anti-inflammatory drugs without the possible side effect of promoting bacterial infection.
Keywords: intestine